Barren Ground: Re-Conceiving Honour and Shame in the Field of Mediterranean Ethnography - Coombe, Rosemary J. (Anthropologica, 2022)
Despite the differences in perspective that define the field, ethnographers of Mediterranean societies consider the cultural values of honour and shame in a remarkably consistent and theoretically impoverished manner. The article attempts to demonstrate that the rhetorical strategies of structural functionalism continue to characterize discussions of honour and shame in Mediterranean societies, even when anthropologists appear to have rejected this theoretical paradigm. Arguing that to conceptualize the values of honour and shame as a type of juridical code does representational violence to the lives and experiences of Mediterranean peoples, the author advocates a practice-oriented theoretical approach to these cultural values that is more sensitive to social relations of inequality and difference.